An examination of health promotion and social inclusion activities: A cross-sectional survey of Australian community Men's Sheds. - Wilson, N.; Cordier, Reinie; Parsons, Richard; Vaz, Sharmila; Ciccarelli, Marina (Australian Health Promotion Association, 2018)
ISSUE ADDRESSED: The activities and well-being outcomes from participating at Men's Sheds are the focus of a growing body of research. Although many Men's Sheds have a clear health or social philosophy, this does not always translate into health and social activities. METHOD: This cross-sectional survey explored the health promotion and social inclusion activities of Men's Sheds and features of Sheds that predict greater levels of these activities. All Australian Men's Sheds were invited to participate. Based on survey responses, Sheds were classified as "active" or "not active" in health promotion and social inclusion, which formed the main survey outcomes. Profiles of the responding Sheds were summarised and compared against the main survey outcomes. Multivariate logistic regression analyses explored the profile variables associated with "active" Sheds. RESULTS: Responses from 300 Sheds indicated 37% and 70% of Sheds were "active" in health promotion and social inclusivity respectively. Number of members, members with mental illness or of Indigenous descent, providing meals and targeting war veterans were associated with health promotion. Having five or more members with a disability, members with English as a second language, targeting of war veterans were associated with social inclusiveness. CONCLUSIONS: Men's Sheds may serve as a unique community resource to reduce barriers of access to preventative health care, education and social connectedness, especially for marginalised members and those living in rural communities. SO WHAT?: A proportion of Men's Sheds reflects the health and well-being exemplars mentioned in the National Male Health Policy that can help to counter the social determinants of poor health, particularly for marginalised males.